Pengembangan Materi Ajar Sosiologi Berbasis Local Wisdom Maesa-Esaan di SMA Negeri 3 Tondano - Abdul Rasyid Umaternate; Siti Fathimah (JUPE : Jurnal Pendidikan Mandala, 2022)
ABSTRACT This research is a continuation of previous research on the Utilization of Local Wisdom as a Learning Resource by Sociology Teachers at SMA Negeri 3 Tondano (Case Study on Sociology Learning Class X) in 2022, where in this study found some local wisdom of the Minahasa community that can be used in Sociology teaching materials in SMA class X are tailored to the basic competencies and core competencies as well as the objectives of learning sociology itself. The long-term goal of this research is to preserve and protect local cultures from being eroded by the currents of social change, with a specific target of innovation to produce a textbook based on local wisdom of the Minahasa Community through maesa-esaan. This study uses a development (R&D) method, namely developing a class X Sociology textbook based on local wisdom, which must have several components, namely the material feasibility component, the presentation feasibility component, the linguistic feasibility component, with the aim of producing a good textbook and provide a sociology teacher's perspective in providing a lesson. The development of textbooks uses a 4D model from Thiagarajan (1947) whose development model consists of four stages of development, namely define, design, develop, and dessiminate or be adapted into a 4-P model, namely Definition, Design, Development and Deployment. In this study, the development of textbooks was simplified only to the design stage, so that the material that had been developed was only used for Class X high school students at SMA N 01 Tondano, without being distributed to other schools. To achieve this goal, this research will be carried out in one year starting from a preliminary study and proceeding to the preparation of draft teaching materials. The product produced in this research is a draft of class X Sociology teaching materials based on local wisdom maesa-esaan. This research is expected to later be able to contribute to the quality of learning for Class X high school students in their daily lives which is also a place for enculturation and preservation of the culture of the Minahasa community itself. Based on the results of the analysis of the material, presentation and language, the objectives and teaching materials were formulated in the Class X Sociology subject. The teaching materials were designed and developed through local wisdom groups.